Determination of nucleobase-pairing free energies from rotamer equilibria of 2-(methylamino)pyrimidines - Štoček, Jakub Radek; Bártová, Kateřina; Čechová, Lucie; Šála, Michal; Socha, Ondřej; Janeba, Zlatko; Dračínský, Martin (Chemical communications (Cambridge, England), 2019)
A fast straightforward method for the determination of free energies of modified nucleobase pairing is proposed. The method is based on the nuclear magnetic resonance (NMR) spectroscopy monitoring of conformational changes of 2-(methylamino)-pyrimidines upon intermolecular binding.